Linear Control Method for Arch Ring of Oblique-Stayed Buckle Cantilever Pouring Reinforced Concrete Arch Bridge - Zengwu Liu; Jianting Zhou; Yuexing Wu; Xing You; Yinghao Qu (Advances in Civil Engineering)
Yelang Lake Bridge is the largest cantilevered single-chamber reinforced concrete arch bridge in China, with a net span of 210 m. In this article, an equation for positioning the height of the formwork before pouring of the arch ring segment was derived, which was suitable for the construction control of the long-span reinforced concrete arch bridge such as the Yelang Lake Bridge. The arch ring segment elevation calculation equation was derived under the two typical working conditions that the concrete pouring of the arch ring segment is completed and the buckle cable and anchor cable tensioning are completed. In addition, two typical working conditions of arch ring segment concrete pouring and cable tensioning were evaluated. Then, a new type of cradle and loading test of the cradle, which meet the requirements of the long segment pouring of the arch ring, were introduced. Finally, the measurement deviation during the construction of the arch segment was analyzed. The linear control results of the arch ring showed that the arch ring segment elevation calculation formula could effectively ensure the accuracy of the arch ring segment construction process under the two typical conditions of completion of concrete pouring of the arch ring segment and completion of the buckle and anchor cable tensioning. The maximum deviation is only 3.1 mm. The line shape after the completion of the arch ring construction was in good agreement with the target line shape, and the deviation between the measured value and the target value was only 2.5 cm, which met the engineering requirements.